PENGARUH DOSIS PUUK KANDANG SAPI TERHADAP PERBAIKAN BEBERAPA SIFAT FISIK, KIMIA DAN BIOLOGI TANAH PADA KONDISI JENUH AIR DAN KAPSITAS LAPANG - Julio Correia (Agriculture Faculty of Flores University, 2013)
Soils are the main media for the growth of crops, the low yield of crops is always related to soil physical, chemical and biological soil conditions. Cattle manure is an organic fertilizer known well before chemical fertilizer. Many types of research on the use of cattle manure to ameliorate physical, chemical and biological soil properties have been conducted, but the optimum rates of cattle manure especially on sandy soil have never been found. This fact may be caused by leaching of organic materials and nutrients to deeper soil layer unreachable by roots. An experiment was conducted in a plastic house using sandy soils from the district of Kubu, Karangasem regency, with the objectives of studying the effects of rates of cattle manure on physical, chemical and biological properties f soils and the effects of inundated and water field capacity of soils on leaching of nutrients in the soils. The experiment was conducted from June until August 2010. The design used was a split-plot design consisted of four rates of cattle manure (0, 10, 20 and 30 t ha-1) as main plots and two water status of soils (inundated and water capacity) as subplots, with three replications. The results of the experiment indicated that cattle manure is able to ameliorate some of the soil physical properties as bulk densities (g cm-3), soil water status (%), soil permeability (cm hour-1) and total soil pores (%), and increased soil pH, C-organic content (%), C/N ratio, NPK and biological properties of soils of low nutrients status of sandy loam brown regosol soils derived from Vulcan intermediary. The results of the experiment also indicated the occurrence of leaching of organic materials and NPK nutrients to 20-40 cm layer. Based on the experiment results it is to suggest to the farmers that the use of cattle manure should be combined with synthetic chemical fertilizer in several applications during growth periods, but this required further researches.